A Novel Hypogenetic Chaotic Jerk System: Modeling, Circuit Implementation, and Its Application. (4th May 2020) - Liu, Jiancheng; Rajagopal, Karthikeyan; Lei, Tengfei; Kaçar, Sezgin; Arıcıoğlu, Burak; Çavuşoğlu, Ünal; Kökçam, Abdullah Hulusi; Karthikeyan, Anitha
Abstract : When revising the polarity and amplitude information in the feedback, a unique hypogenetic jerk system was obtained which has two controllers to switch the equilibria between stable and unstable. After providing some basic dynamical analysis, an electronic circuit was implemented, and the phase trajectory in the oscilloscope agrees with the numerical simulation. Further exploration shows that this unique chaotic system has superior performance as a random number generator or in voice encryption application.